MENINGKATKAN KEMAMPUAN MENULIS KARANGAN MELALUI MODEL CONTEKSTUAL TEACHING AND LEARNING PADA SISWA KELAS IV SDN - Mokoagow, Sri Nora Aulia; Pulukadang, Wiwy Trianty; Husain, Rusmin; Monoarfa, Fidyawati; Husain, Rustam I. (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study was motivated by the low essay writing ability of elementary school students, particularly fourth-grade students at SDN 12 Anggrek, North Gorontalo Regency. Many students still perceive writing as a difficult task due to limited skills in identifying main ideas, organizing storylines, and selecting appropriate vocabulary and sentence structures. To address these challenges, the Contextual Teaching and Learning (CTL) model was implemented as an instructional approach that connects learning materials with students’ real-life experiences, thereby making the writing process more meaningful and engaging. The purpose of this research was to determine the effectiveness of the CTL model in improving students’ essay writing skills. The study employed Classroom Action Research (CAR), conducted in two cycles. Data were collected through essay writing tests, classroom observations, and documentation. The findings revealed a consistent improvement in students’ performance across the cycles. In Cycle I, Meeting I, 6 students (50%) achieved the competency criteria, which increased to 8 students (67%) in Meeting II. In Cycle II, the number of students meeting the criteria rose to 10 students (83%). These results indicate that the CTL model is effective in enhancing the essay writing ability of fourth-grade students at SDN 12 Anggrek. ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya kemampuan menulis karangan pada siswa sekolah dasar, khususnya siswa kelas IV SDN 12 Anggrek Kabupaten Gorontalo Utara. Kegiatan menulis masih dianggap sulit oleh sebagian besar siswa karena keterbatasan dalam menemukan gagasan pokok, menyusun alur cerita, serta memilih kata dan kalimat yang tepat. Untuk mengatasi permasalahan tersebut, diterapkan model Contextual Teaching and Learning (CTL) sebagai pendekatan pembelajaran yang mengaitkan materi dengan pengalaman nyata siswa sehingga proses menulis menjadi lebih bermakna. Penelitian ini bertujuan untuk mengetahui sejauh mana penerapan model CTL dapat meningkatkan kemampuan menulis karangan siswa. Metode yang digunakan adalah penelitian tindakan kelas (PTK) yang dilaksanakan dalam dua siklus, dengan teknik pengumpulan data melalui tes menulis karangan, observasi proses pembelajaran, dan dokumentasi. Hasil penelitian menunjukkan adanya peningkatan kemampuan menulis dari setiap siklus. Pada siklus I pertemuan I, sebanyak 6 siswa (50%) mencapai kategori mampu, meningkat menjadi 8 siswa (67%) pada pertemuan II. Pada siklus II, jumlah siswa yang mencapai kategori mampu bertambah menjadi 10 siswa (83%). Temuan ini membuktikan bahwa penerapan model CTL efektif dalam meningkatkan kemampuan menulis karangan siswa kelas IV SDN 12 Anggrek.